The Meningkatkan Aktivitas dan Hasil Belajar dengan Problem Based Learning Berbasis Pendekatan Andragogi - Raharjo, Semiono (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study aims to determine whether Problem Based Learning (PBL) based on andragogy approach can improve students' activities and learning outcomes on Optical Tools material. The research was conducted using Classroom Action Research method. The research subjects were students of SMAN 1 Piyungan class XI MIPA-2 totaling 36 students. One class was subjected to action, namely learning with PBL model based on andragogy approach. Data on student learning activities were obtained from student learning activity observation sheets. The success indicator for student learning activity is at least 75% and the indicator of student learning outcome completeness individually is at least 75 and classically at least 85% students are complete. The percentage of classical completeness increased after being given action in cycle I with a score of 78, in cycle II it increased with an average score of 81, while in cycle III it increased with an average score of 88. Student learning activities have increased from cycle to the next cycle, namely 26% in cycle I, 57% in cycle II, and 96% in cycle III. With these results, it can be concluded that the PBL model based on the andragogy approach can increase students' activity and learning outcomes in class XI MIPA-2 SMAN 1 Piyungan on the material of Optical Tools.